Evaluation of the urban infrastructure network in a sub-basin in the Municipality of Itaperuna, State of Rio de Janeiro, Brazil (Research, Society and Development, 2020)
The rapid growth of medium and large Brazilian cities in recent decades has intensified the process of density and one of the consequences is the undue occupation of urban watershed areas. This article aims at the urban diagnosis of a contribution sub-basin in Itaperuna, a municipality of a semi-urbanized area of 1,105.341 km² in the Northwest of the State of Rio de Janeiro, Brazil. The methodology was based on the evaluation of the sub-basin according to the criteria of infrastructure (paving and drainage), social (population and housing density) and environmental (occurrence of floods) based on the field cadastral survey and database analysis of the urban infrastructure network. The results showed that the sub-basin presented a deficient infrastructure system with regard to paving and drainage of urban roads, in addition to the conservation and preservation of the existing watercourse. From the diagnosis presented, it is expected that this study will contribute additionally as a tool for decision-making of the relevant public authorities, taking into account studies and technical prerogatives fundamental to the implementation of an effective urban drainage system, ensuring the well-being of the population living in the region.